2002
DOI: 10.2337/diacare.25.8.1378
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Diabetes in the Kingdom of Tonga

Abstract: RESEARCH DESIGN AND METHODS -A randomly selected representative national sample of 1,024 people aged Ͼ15 years was surveyed. Each participant had fasting blood glucose and HbA 1c measured. Subjects with a fasting blood glucose Ͼ5.0 mmol/l (90 mg/dl) and Ͻ11.1 mmol/l (200 mg/dl) or a fasting blood glucose Յ5.0 mmol/l and an HbA 1c Ͼ6.0% and every fifth subject with a fasting blood glucose Յ5.0 mmol/l and a normal HbA 1c had a 75-g oral glucose tolerance test (OGTT). A total of 472 individuals had an OGTT based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 17 publications
2
40
1
Order By: Relevance
“…This remains today as the highest national diabetes prevalence yet described. Further studies (14)(15)(16) in other Pacific nations by our group and others have confirmed the high prevalence rates.…”
Section: The Epidemiology Of Type 2 Diabetessupporting
confidence: 54%
“…This remains today as the highest national diabetes prevalence yet described. Further studies (14)(15)(16) in other Pacific nations by our group and others have confirmed the high prevalence rates.…”
Section: The Epidemiology Of Type 2 Diabetessupporting
confidence: 54%
“…For this analysis, nine datasets from the DETECT-2 database were selected, which were representative of people from a diverse range of ethnic backgrounds (Northern and Southern Europe, U.S., Indian subcontinent, Asia, Australia, Pacific Islands, and Africa) (2,8,(21)(22)(23)(24)(25)(26)(27). For the Third National Health and Nutrition Examination Survey (NHANES III), only the subsample of individuals that underwent a 75-g oral glucose tolerance test was included (2).…”
Section: Research Design Andmentioning
confidence: 99%
“…Early diagnosis is therefore of major importance, since normalisation of glycaemia may reduce the risk of these diabetes-related conditions 7 . Unfortunately, several studies in different countries have reported that up to half of all subjects with diabetes are undiagnosed 8,9 . No data for undiagnosed diabetes are available for the Moroccan population.…”
mentioning
confidence: 99%